Teori Kutukan Sumber Daya Alam (Resource Curse) dalam Perspektif Ilmu Politik - Ahmad Sholikin (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2020)
Overall, the empirical literature related to "Natural Resource Curse" can be divided into three main strands; first, which examines the impact of natural resources and economic growth. Literrature studies explain economic outcomes in countries rich in natural resources in part operate from a neoclassical / public choice or behaviorist perspective. The second literacy study; examine the impact of natural resources on democracy or democratic institutions. In one of his previous contributions, Ross (2001) not only discussed the mechanism and channel but also examined it empirically. Ross points out that natural resources in the form of oil and mineral wealth are negatively related to the size of democracy. He also found tentative support for three causal mechanisms connecting oil and authoritarian rule. Third empirical literature review; examines the impact of natural resources on institutional governance measures, such as corruption. Ades and Di Telia (1999), empirically and theoretically look for the determinants of corruption, the results include the impact of natural resources. Using the share of fuel and mineral exports in total exports, they invaded whether an increase in this section led to an increase in corruption in the 1980s and 1990s.